A Note on Gamma Distributed Lags - Hiroki Tsurumi (Queen's University, Department of Economics, 1969)
This paper talks about the Solow (10) generalized Koyck's method for distributed lags to a family of J-shaped or unimodel lag distributions given by the Pascal distributions. Jorgenson (5) advances it to what he calls the general Pascal distribution.
Keywords: 330